Inhabitants of the White Sea coastal ice during the early spring period. - Sazhin, Andrey F; Ratkova, Tatyana N; Kosobokova, Ksenia N (PANGAEA, 2004)
In April 2002 at four stations located in the vicinity of the White Sea Biological Station, Zoological Institute, Russian Academy of Sciences (Chupa Inlet, Kandalaksha Bay) ice samples were taken. It was shown that phototrophic and heterotrophic flagellates inhabit White Sea ice together with diatoms and dinoflagellates. In addition to three well-known communities, namely, assemblages of the lower ice surface, assemblages of pore channels, and interstitial communities, an infiltration assemblage and that of melt ice pools not described for the White Sea before were found in the White Sea ice. Biomass of ice algae varied from 130 to 1400 mg C/m**2. Maximum biomass was observed in the lower part of ice (from 2.5 to 36 g C/m**3 or 50-720 mg C within the lower 2-4 cm layer). It is shown that beginning of spring algal growth in the White Sea should be related not to the period of release of the sea from ice and subsequent water warming, but to the period of ice melting at the sea-ice interface and, correspondingly, to increase in its illumination. Sea-ice algae entering water from ice long before beginning of spring ''bloom'' of typical pelagic phytoplankton are grazed by planktonic heterotrophs directly under sea ice and serve at this period as a basis for the pelagic food chain.
Contribution of different algae groups in their total biomass and biomass of Infusoria and Nematoda
Keywords: Algae, biomass as carbon; Archive of Ocean Data; ARCOD; Carbon biomass estimation (unspec.); Chupa-2002-1; Chupa-2002-2; Chupa-2002-3; Chupa-2002-4; Date/Time of event; DEPTH, sediment/rock; Diatoms, biomass as carbon; Flagellates, biomass as carbon; Infusoria, biomass as carbon; MULT; Nematoda, biomass as carbon; White Sea